 ## Book: NCERT - Mathematics

### Chapter: 9. Algebraic Expressions and Identities

#### Subject: Maths - Class 8th

##### Q. No. 4 of Exercises 9.5

Listen NCERT Audio Books - Kitabein Ab Bolengi

4
##### Simplify.(i) (ii) (iii) (iv) (v) (vi) (vii)(m2 - n2m) 2 + 2m3n2(viii) (i) Using Identity (a - b) 2 = a2 - 2ab + b2 In the given expression a = On substituting these values in the above identity, we get  (ii) Using Identity a2 - b2 = (a + b)(a - b)

In the given expression a = On substituting these values in the above identity, we get  (iii) Using Identity (a - b)2 = a2 - 2ab + b2 for finding the value of In the given expression a = On substituting these values in the above identity, we get  ………………………………………………..(i)

Using Identity (a + b) 2 = a2 + 2ab + b2 for finding the value of In the given expression a = On substituting these values in the above identity, we get  ………………………………………………..(ii)

On Adding equations (i) and (ii), we get  (iv) Using Identity (a + b) 2 = a2 + 2ab + b2 for finding the value of In the given expression a = On substituting these values in the above identity, we get  ………………………………………………..(i)

Using Identity (a + b) 2 = a2 + 2ab + b2 for finding the value of In the given expression a = On substituting these values in the above identity, we get  ………………………………………………..(ii)

On Adding equations (i) and (ii), we get  (v) Using Identity (a - b) 2 = a2 - 2ab + b2 for finding the value of In the given expression a = On substituting these values in the above identity, we get  ………………………………………………..(i)

Using Identity (a - b) 2 = a2 - 2ab + b2 for finding the value of In the given expression a = On substituting these values in the above identity, we get  ………………………………………………..(i)

On Subtracting equations (ii) from (i), we get   (vi) Using Identity (a + b)2 = a2 + 2ab + b2 for finding the value of In the given expression a = On substituting these values in the above identity, we get  ………………………………………………..(i)

On Subtracting from (i), we get  (vii) (m2 - n2m)2 + 2m3n2

Using Identity (a - b) 2 = a2 - 2ab + b2 for finding the value of In the given expression a = On substituting these values in the above identity, we get  ………………………………………………..(i)

On Subtracting from (i), we get  (viii) Using Identity (a - b) 2 = a2 - 2ab + b2 for finding the value of In the given expression a = On substituting these values in the above identity, we get  ………………………………………………..(i)

On Adding in eqn (i), we get  First Find the value of RHS Using Identity (a + b) 2 = a2 + 2ab + b2 for finding the value of In the given expression a = On substituting these values in the above identity, we get  ………………………………………………..(ii)

Therefore from eqn (i) and equ (ii) we found that LHS = RHS

4

1
2
1
4
5
6
7
8